1996
DOI: 10.1002/(sici)1097-4636(199603)30:3<305::aid-jbm5>3.3.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Pillared‐surface microstructure and soft‐tissue implants: Effect of implant site and fixation

Abstract: Previous work with subcutaneous implants in a rat animal model has shown that pillarlike surface microstructure will reduce fibrosis and enhance blood vessel approximation to the implant surface when compared with nontextured controls. This study was designed to determine the effect of microtissue anatomy and implant site on the observed response, as well as the effect of implant fixation. The lateral posterior sites were found to contain a fat pad which produced a dramatically reduced fibrosis for the microst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 0 publications
3
32
0
Order By: Relevance
“…As seen in previous studies, tissue attachment to subcutaneous implants is increased when the implant is roughened or porous coated 10, 31, 5355. In a study performed by Kim and colleagues, surfaces with varying roughness or grooves resulted in greater tissue attachment and less fibrous capsule formation compared to the smooth surfaces, which had a thick fibrous capsule formation, similar to the presented results.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…As seen in previous studies, tissue attachment to subcutaneous implants is increased when the implant is roughened or porous coated 10, 31, 5355. In a study performed by Kim and colleagues, surfaces with varying roughness or grooves resulted in greater tissue attachment and less fibrous capsule formation compared to the smooth surfaces, which had a thick fibrous capsule formation, similar to the presented results.…”
Section: Discussionsupporting
confidence: 89%
“…Smooth surface implants have less surface area for tissue attachment, and the fibrous capsule which develops around the surface allows the implants to move within the soft tissue making it difficult for any soft tissue seal to form 53. It is generally believed that any “mechanical irritation” produced by stress and movement at an implant interface yields a thicker fibrous capsule formation 31, 53, which was observed in this study. The absence of soft tissue attachment to the smooth surfaces was seen during the histological processing as the tissue would separate from the implant; whereas, this was not observed with the porous implants.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The most probable source for the foreign body induction is the macrophages close to the filter surface. Surface characteristics of the filters then become more important, and a biomaterial with a surface structure that allows ingrowth of the surrounding tissue will likely make the initial inflammatory reaction subside and become incorporated into tissue 35, 36. An important factor in these events is most probably the mechanical stability2, 7 at the implant–tissue interface, where a persistence of interfacial shear will sustain the inflammatory reaction and foreign body capsule formation 22, 37…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, silicone implants provided with pillars and pits of 2 to 8 mm showed less mononuclear cell attachment, and resulted in a thinner capsule. Similarly, Picha and coworkers 81 found that large (500-mm) pillars reduced inflammation and capsule formation around silicone implants.…”
Section: Effects Of Microtextures In Vivomentioning
confidence: 99%